Hydrogen Sulfide, an Endogenous Stimulator of Mitochondrial Function in Cancer Cells - Szabo, Csaba (Cells, 2021)
Hydrogen sulfide (H(2)S) has a long history as toxic gas and environmental hazard; inhibition of cytochrome c oxidase (mitochondrial Complex IV) is viewed as a primary mode of its cytotoxic action. However, studies conducted over the last two decades unveiled multiple biological regulatory roles of H(2)S as an endogenously produced mammalian gaseous transmitter. Cystathionine γ-lyase (CSE), cystathionine β-synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (3-MST) are currently viewed as the principal mammalian H(2)S-generating enzymes. In contrast to its inhibitory (toxicological) mitochondrial effects, at lower (physiological) concentrations, H(2)S serves as a stimulator of electron transport in mammalian mitochondria, by acting as an electron donor—with sulfide:quinone oxidoreductase (SQR) being the immediate electron acceptor. The mitochondrial roles of H(2)S are significant in various cancer cells, many of which exhibit high expression and partial mitochondrial localization of various H(2)S producing enzymes. In addition to the stimulation of mitochondrial ATP production, the roles of endogenous H(2)S in cancer cells include the maintenance of mitochondrial organization (protection against mitochondrial fission) and the maintenance of mitochondrial DNA repair (via the stimulation of the assembly of mitochondrial DNA repair complexes). The current article overviews the state-of-the-art knowledge regarding the mitochondrial functions of endogenously produced H(2)S in cancer cells.